Dispersal strategies of juvenile pike (Esox lucius L.): Influences and consequences for body size, somatic growth and trophic position. Issue 2 (28th November 2019) - Nyqvist, Marina J.; Cucherousset, Julien; Gozlan, Rodolphe E.; Beaumont, William R.C.; Britton, J. Robert
Abstract: Individual variability in dispersal strategies, where some individuals disperse and others remain resident, is a common phenomenon across many species. Despite its important ecological consequences, the mechanisms and individual consequences of dispersal remain poorly understood. Here, riverine Northern pike ( Esox lucius ) juveniles (age 0+ (young‐of‐the‐year) and 1+ years) were used to investigate the influence of body size and trophic position (at capture) on the dispersal from off‐channel natal habitats and the subsequent consequences for body sizes, specific growth rate and trophic position (at recapture). Individuals that dispersed into the river ("dispersers") were not significantly different in body size than those remaining on nursery grounds ("stayers"). For trophic position, 0+ dispersers were of significantly lower trophic position than stayers, but with this not apparent in the 1+ fish. Following dispersal into the river, the dispersers grew significantly faster than stayers and, on recapture, were significantly larger, but with no significant differences in their final trophic positions. Early dispersal into the river was, therefore, not associated with early dietary shifts to piscivory and the attainment of larger body sizes of individuals whilst in their natal habitats, contrary to prediction. These results suggest that despite an increasing risk of mortality for individuals dispersing early from natal areas, there are long‐term benefits via elevated growth rates and, potentially, higher fitness. Such early dispersal behaviour could be driven by early competitive displacement.